Transformasi Epos I La Galigo dalam Bentuk Cerita Bergambar Sebagai Media Visualisasi Pembelajaran IPS: Inovasi atau Tantangan? - Hasni Hasni; Nana Supriatna; Sapriya Sapriya; Murdiyah Winarti; Andi Ima Kusuma (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
This research is based on important developments in historiography which are critical of tradition as a source of history. Traditional cultural heritage can be found in folklore around the world, including Bugis folklore in Epic I La Galigo which is a source of personality identity for South Sulawesi, Indonesia which must be passed on to the younger generation. This condition demands that the Bugis folklore, Indonesia in the First Epic of La Galigo must be transformed according to the demands of technology with fun, creative and innovative learning. The purpose of this study is to examine the cultural value of Bugis folklore, South Sulawesi, Indonesia in the Epic I La Galigo as a source of social studies learning, and to find out the transformation of Bugis I La Galigo folklore as an innovation or challenge-based social studies learning resource. The research method used is the literature study method by reviewing the literature from various criteria ranging from books, journals or articles and documentation at the La Galigo Museum. The results of the study show that the cultural values in Epic I La Galigo are: (1) Siri' and Pesse', (2) Sumangeq and Inninawa, (3) Preservation of the environment, (4), Lempuk (honest), (5) Getteng (steadfast on the establishment) and (6) Mutual respect. The transformation of Bugis folklore in I La Galigo is an innovative social studies teacher's creative pedagogy by improvising through the development of material content into three media: (1) an oral tradition based on picture story media, (2) an oral tradition based on video animation media as visualization, and (3) webtoon-based media. This research is expected to be a responsive social studies learning transformation movement with a technology-based approach, so that teachers and students are qualified and skilled at innovating through folklore.